2016
DOI: 10.1002/2015jb012500
|View full text |Cite
|
Sign up to set email alerts
|

Two types of volcanic tremor changed with eruption style during 1986 Izu‐Oshima eruption

Abstract: Volcanic tremor provides clues to magma migration pathways so that tremor source location is expected to be an efficient tool for tracking dynamic behavior of magma in evolution of eruptive activity. However, clear evidence, which connects between temporal variation in volcanic tremor and evolution of eruption style, is still lacking. We have analyzed volcanic tremors occurred during 1986 Izu‐Oshima eruption using recently digitized data. The results present a clear link between eruption styles, waveform varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Equation (1) is used in a limited frequency band, and the root-mean-square (RMS) is frequently used to evaluate the amplitude of continuous tremor (Battaglia & Aki, 2003;Battaglia et al, 2005;Kurokawa et al, 2016;Ogiso & Yomogida, 2012). The power spectral density (PSD) is calculated by summing those of the three components of the seismometer data in a moving time window with a length of 10 s (Figures 2c and 2d).…”
Section: Source Location Methods Using Amplitude Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (1) is used in a limited frequency band, and the root-mean-square (RMS) is frequently used to evaluate the amplitude of continuous tremor (Battaglia & Aki, 2003;Battaglia et al, 2005;Kurokawa et al, 2016;Ogiso & Yomogida, 2012). The power spectral density (PSD) is calculated by summing those of the three components of the seismometer data in a moving time window with a length of 10 s (Figures 2c and 2d).…”
Section: Source Location Methods Using Amplitude Distributionmentioning
confidence: 99%
“…Source location of volcanic tremor is an efficient tool for monitoring volcanic activity. In determining the source location of tremor, spatial distribution of tremor amplitude is used in many studies (Battaglia and Aki, ; Battaglia et al, ; Cannata et al, ; Kumagai et al, , ; Kurokawa et al, ; Ogiso & Yomogida, ). The method assumes the seismic amplitude distribution by A(Di)=A0SiDiαexp()BDi,B=πfQc, where A 0 is the source amplitude, D i is the distance from the source, and S i is the site amplification factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Battaglia and Aki (2003) demonstrated that the eruptive tremor sources at Piton de la Fournaise volcano were good indicators of the locations of eruptive fissures; in a subsequent study demonstrated that the cumulative amplitude of tremor recorded throughout an eruption could be used to estimate the volume of lava erupted. Several studies have also shown that analyzing the spectral content and location of volcanic tremor can help track the evolution of magma migration (Di Lieto et al, 2007;Jellinek & Bercovici, 2011;Kurokawa et al, 2016) The application of machine learning (ML) techniques to the analysis of geophysical signals has become widespread in diverse settings such as the analysis of laboratory experiments Rouet-Leduc et al, 2017;Rouet-Leduc, Hulbert, Bolton, et al, 2018), tracking slow-slip in real Earth (Rouet-Leduc, , and phase association for the development of earthquake catalogs to © 2020. The Authors.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are useful for locating VT earthquakes with impulsive onsets, but LP events and tremor have emergent onsets, and location of their hypocenters by those methods is difficult or impossible. To overcome the limitations of the traditional methods, the amplitude source location (ASL) method proposed by Battaglia and Aki [] has been used to locate various volcano‐seismic signals including LP events and tremor [ Battaglia et al ., ; Battaglia et al ., , ; Kumagai et al ., , , , , ; Ogiso and Yomogida , , ; Ogiso et al ., ; Kurokawa et al ., ]. The ASL method uses high‐frequency seismic amplitudes and assumes isotropic radiation of S waves.…”
Section: Introductionmentioning
confidence: 99%